Analisis Survey Tracer Studi Program Studi Teknik Informatika Strata 1 Sekolah Tinggi Teknik PLN Tahun 2014 - Iriansyah BM Sangadji (KILAT, 2015)
Tracer Study is an effective medium that is used to track the whereabouts and condition of alumni. The activities of alumni tracer study / survey carried out based on the desire to capture information from the alumni as an evaluation and development of the college. STT PLN general and Informatics Engineering program in particular by making use of the survey data, can find out about the absorption process and the position of graduates in order to improve the quality of continuous learning by improving the curriculum, improving the quality of teachers, and the adjustment and improvement of learning systems. Armed with a variety of information obtained from the state of alumni of the program of study / campus can prepare preventive measures in order to overcome the gap between graduates and the needs of users graduates. In the course of this year Tracer Study will be recorded graduation last 2 years that graduation 24 November 2012 and April 27 2013.Hasil survey conducted and analyzed and processed by using statistical methods to look at the behavior of alumni before and after employment. Alumni views based on questions contained in the link tracer STT PLN. The analysis will show a measure of value. The analysis will show a measure of value and description of the mapping of the Informatics Engineering program alumni STT PLN as the guidelines issued by the Directorate General of Higher Education.